Huge multinodular goiter with retrosternal extension, a challenge to both surgeon and anesthetist: a case report - Mohammad, Benazeer H.; Manju; Pusuluri, Rahul; Pandey, Srijan; Garg, Ashish; Saini, Rajat (International Journal of Research in Medical Sciences, 2024)
Retrosternal goitre, defined as over 50% of the thyroid mass extending below the thoracic inlet, is a rare presentation of goitre. These cases are particularly observed among females in their 5th and 6th decades. Symptoms like breathlessness, facial flushing, and dysphagia, alongside complications like superior vena cava syndrome, increase morbidity. Surgery is the management of choice. While most cases are managed surgically via a cervical approach, some require thoracic intervention due to airway and neurovascular compression, including displacement of critical vessels like the subclavian and carotid arteries. We present a case of 63-year-old female with a huge euthyroid multinodular goiter with no pressure symptoms. Contrast enhanced computed tomography (CECT) neck was suggestive of bilateral enlargement of thyroid nodules, with left sided lobe also getting an additional supply from left brachiocephalic artery. Surgery of retrosternal goitre commonly involves a cervical approach, but thoracotomy maybe needed in cases of malignancy, redo thyroid surgery, or mediastinal goitres. Careful dissection to avoid damage to recurrent laryngeal nerve (RLN) and mediastinal structures is required, especially when nodules extend into the thorax. Tracheomalacia and vocal cord dysfunction, are rare but serious complications. Anesthesia challenges include difficult airway management due to tracheal deviation. Awake fibreoptic intubation is preferred, and patients may require intubation for 24 hours postoperatively due to anticipated airway edema. Large, long-standing retrosternal goitres require thorough preoperative surgical and anesthetic workup, often necessitating ear, nose and throat (ENT) and thoracic surgery backup, with CECT with angiograph aiding operative planning.